Functional Magnetic Resonance Imaging Versus Kidney Biopsy to Assess Response to Therapy in Nephrotic Syndrome: A Case Report - Anna Caroli; Andrea Remuzzi; Barbara Ruggiero; Camillo Carrara; Paola Rizzo; Paolo Brambilla; Piero Ruggenenti; Giuseppe Remuzzi (Kidney Medicine, 2020)
In recent years, kidney functional magnetic resonance imaging (MRI) has seen great advances, with several cross-sectional studies demonstrating correlations between MRI biomarkers and glomerular filtration rate. However, the potential of MRI to monitor response to therapy in kidney disease remains undescribed. In this case report, a man in his 40s with drug-resistant membranous nephropathy was addressed to ofatumumab therapy. He underwent kidney biopsy before and 2 years after treatment and repeat non–contrast-enhanced MRI of the kidney every 6 months. An age- and sex-matched healthy volunteer was included as a normal control. The patient showed a striking positive immunologic response to therapy. Repeat MRI of the kidney documented progressive kidney functional recovery, with a significant widespread increase in kidney diffusivity, assessed using diffusion-weighted imaging, paralleling the increase in glomerular filtration rate and regression of albuminuria. Renal blood flow and ultrafiltration coefficient, assessed using phase-contrast MRI, significantly increased, suggesting an increase in filtration fraction. This case report provides the first clinical evidence in support of MRI of the kidney as a tool to noninvasively monitor pathophysiologic changes occurring in response to treatment. Although kidney biopsy remains critical for diagnosis, functional MRI of the kidney has promise for monitoring disease progression and response to therapy.